Klausa Non-Finit X-COMP dan X-ADJ dalam Berita Banjir dan Longsor Sumatera 2025: Kajian Teori LFG - Dini Eka Maulida; Agus Subiyanto; Khairina Nasution (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2026)
This study investigates the use of non-finite clauses realizing X-COMP and X-ADJ functions in international news texts on natural disasters published by BBC News and Reuters. The study aims to compare the frequency of X-COMP and X-ADJ occurrences and to describe their syntactic constructions within the framework of Lexical Functional Grammar (LFG), focusing on the relationship between c-structure and f-structure. The data consist of four online news articles reporting floods and landslides in Sumatra in 2025, analyzed using a qualitative descriptive approach through close reading and note-taking techniques. The findings reveal that out of 50 identified non-finite clauses, X-ADJ occurs more frequently than X-COMP, with 32 and 18 instances respectively. This dominance of X-ADJ is consistently observed in both media sources, indicating that non-finite clauses are primarily employed as optional adjuncts to provide situational information such as purpose, manner, and conditions of events. Syntactically, X-COMP is realized as an open clausal complement subcategorized by the main predicate and involves subject control, whereas X-ADJ functions as an optional open adjunct that does not alter the core argument structure. These results suggest that the use of non-finite clauses in news discourse serves as a syntactic strategy to achieve information density and communicative efficiency in international disaster reporting.